Regional specialization and employment dynamics in transition countries - Iulia Traistaru; Guntram B. Wolff (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
Trade reorientation and transition to a market economy in Central and East European countries have resulted in structural change, i.e. industrial restructuring and labor reallocation across sectors and regions. In the 1990s, many transition countries have experienced considerable decline in output and employment. In this paper we investigate and explain regional differentials in employment change in three transition countries: Bulgaria, Hungary and Romania. We apply a shift-share analysis using a three-factor decomposition and assess the role of industry mix (structural component), region-specific factors (differential component) and regional competitiveness (allocative component) in explaining regional differentials in employment growth. We find that the variance of regional employment growth is driven almost entirely by region-specific factors. Industry mix and regional competitiveness factors play only a minor role in explaining regional employment dynamics in the three countries included in our study.
Keywords: 330